The Role of Islamic Education Philosophy in Forming Self-Concept of Islamic Education Students - Iqbal Amar Muzaki; Taufik Mustofa; Hinggil Permana (Journal of Teacher Training and Educational Research, 2026)
This study aims to analyze the role of Islamic Education Philosophy in shaping the self-concept of undergraduate students in Islamic Religious Education at Universitas Singaperbangsa Karawang. Employing a qualitative approach with a case study method, this research explores students' understanding of key concepts in Islamic Education Philosophy and how this understanding influences their professional and personal identities. Findings indicate that students possess varying levels of comprehension; however, Islamic Education Philosophy significantly contributes to the formation of their self-concept, fostering a sense of responsibility, integrity, and a holistic view of knowledge. Factors such as the quality of lecturer instruction, curriculum relevance, and students' intrinsic motivation are identified as crucial elements influencing this process. The practical implications of this study suggest the need to strengthen pedagogical methods and enhance the integration of philosophical principles within the curriculum, while also encouraging students to actively internalize these values. This study contributes to the theoretical understanding of the relationship between religious philosophy and the development of professional identity in the field of education.